APPLICABILITY OF GENOMIC TECHNOLOGIES FOR IMPROVING IMPORTANT TRAITS IN HORTICULTURAL PERENNIAL CROPS - Ryabushkina , N.A.; Pozharskiy , A.S.; Omasheva , M.Y. (Eurasian Journal of Applied Biotechnology, 2017)
Horticultural perennial crops are cultivated on one-eighth of global agricultural areas and are significant contributors to world food production. Fruits and berries from such crops are recognized as essential for good nutrition and prevention of numerous diseases. However, developing cultivars that meet modern economic and environmental demands require many breeding cycles and a considerable period. Modern varieties are developed to show high quality and yield, and resistance to pathogens and pests. The recent developments in high-throughput DNA sequencing technologies have been exploited to identify the associations between genes and/or genomic intervals controlling important traits and phenotype. These technologies also enable the development of molecular markers for assisted selection and breeding, the introgression of useful traits from wild relatives such as disease resistance, fruit quality, and rootstock characteristics. Genomic methods provide a valuable approach for the selection of traits of interest in seeds or seedlings and for the improvement of breeding efficiency through marker-assisted selection (MAS) and genome-wide association studies (GWAS). The accurate and cost-effective characterization of large collections of diverse wild germplasms supports such breeding initiatives. Grapevines and apples are among the most economically important of perennial crops and are affected by a large number of pathogens. The monogenic nature of many resistance genes has allowed the identification of homologs in wild relatives and enables the development of molecular markers linked to resistance loci. Thus, genomic approaches in combination with traditional breeding methods offer a promising prospect for improving perennial crops.